Efficacy of chemotherapy in patients with HR+/HER2–Invasive lobular breast cancer. (2023) - Yaghi, Marita; Bilani, Nadeem; Dominguez, Barbara; Zerdan, Maroun Bou; Li, Hong; Saravia, Diana; Stone, Elizabeth; Nahleh, Zeina
Highlights: Data on optimal treatment for HR+/HER2- invasive lobular cancer (ILC) remain scarce. Addition of chemotherapy to endocrine therapy didn't benefit overall survival. Lack of added benefit was seen despite high risk of recurrence (OncotypeDX ≥26). Abstract: Introduction: : Invasive Lobular Breast Cancer (ILC) harbors unique clinicopathologic features. Data on optimal treatment modalities focusing on ILC remain scarce. We aim to investigate the benefit of chemotherapy in early-stage hormone receptor-positive (HR+) and human epidermal growth factor receptor-2 negative (HER2-) ILC. Methods: : Female patients with early HR+/HER2- ILC (stages I-III) who underwent surgery were selected from the National Cancer Database (2010–2016) and grouped into four treatment cohorts: surgery only(S), chemotherapy alone (CT), endocrine therapy alone (ET), and combined chemotherapy followed by endocrine therapy (CET). Descriptive and bi-variate statistics summarized baseline characteristics and compared them across cohorts. A secondary analysis accounting for OncotypeDX (ODX) information was performed, stratifying for low (<26) and high (≥26) ODX. Kaplan–Meier (KM) and Cox proportional hazard models evaluated the relationship between treatment modality and overall survival (OS), stratifying for ODX scoring. Results: : N  = 15, 271 patients were included. The CET cohort (29.8%) was more likely to be younger and have no co-morbidities, advanced tumor stage or high ODX score (≥26). No significant difference in OS comparing ET to CET (HR:1.08, 95%CI:0.93–1.26, p  = 0.31) was observed, adjusting for confounders. N  = 5, 561 patients had ODX results available. No significant difference in 5-year OS was observed comparing the ET to CET cohorts, both in patients an ODX score <26 (HR:1.10; 95%CI:0.69–1.76, p  = 0.69) and ODX score ≥26 (HR:1.18; 95%CI:0.51–2.75, p  = 0.69). Conclusion: : Chemotherapy demonstrated no added survival benefit in HR+/HER2- ILC, even in tumors with ODX ≥26. Prospective trials identifying potential subgroups of patients with ILC who could benefit from chemotherapy are needed.